Optimization of steel plate planning for keppel FELS - Ni, Yang (2014)
Keppel FELS is one of the world leaders in offshore unit production and services. And steel plates are the most critical materials to Keppel FELS as their availability will determine the on-time completion and delivery of finished products which normally cost millions of dollars and customers cannot afford a delay while these critical pieces are being built or repaired and stop generating profits.